2011
DOI: 10.1111/j.1365-2036.2011.04592.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric histology in children treated with proton pump inhibitors long term, with emphasis on enterochromaffin cell-like hyperplasia

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
2
11
0
2
Order By: Relevance
“…Although a clear correlation between PPI treatment and g-NETs in humans [18,30,31] is yet to be demonstrated, it has already been established that prolonged PPI-induced acid suppression causes the elevation of circulating gastrin levels in rodents as well as humans [32][33][34][35] and possibly leads to ECL-cell hyperplasia [17,22,36]. In animal safety tests, PPIinduced hypergastrinemia exerts a marked trophic effect on ECL-cell and may induce g-NETs of variable malignancy [22,35,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Although a clear correlation between PPI treatment and g-NETs in humans [18,30,31] is yet to be demonstrated, it has already been established that prolonged PPI-induced acid suppression causes the elevation of circulating gastrin levels in rodents as well as humans [32][33][34][35] and possibly leads to ECL-cell hyperplasia [17,22,36]. In animal safety tests, PPIinduced hypergastrinemia exerts a marked trophic effect on ECL-cell and may induce g-NETs of variable malignancy [22,35,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Certaines des réserves formulées chez l'adulte se posent pourtant avec une acuité renforcée chez l'enfant. On citera par exemple le rôle déterminant du métabolisme du calcium pour la constitution de la masse osseuse, ou encore le risque associé à l'apparition de cellules hyperplasiques connues pour pouvoir évoluer vers une gastrite atrophique [67].…”
Section: Contexte Pédiatriqueunclassified
“…However, studies have shown that the prolonged of PPIs may lead to an increased risk of an infection due to the suppression of stomach acid, which ordinarily acts as the first line of defense. In addition, long-term use of PPIs increases the risk of a number of other side effects, such as the development of hyperplastic polyps and a reduction in the absorption of certain trace elements and vitamins (2)(3)(4). Therefore, it is necessary to investigate novel anti-ulcer drugs with non-toxic side effects, which may replace antacids.…”
Section: Introductionmentioning
confidence: 97%